2019
DOI: 10.1001/jamanetworkopen.2019.10373
|View full text |Cite
|
Sign up to set email alerts
|

Association of Primary Care Clinic Appointment Time With Opioid Prescribing

Abstract: Key Points Question Is the decision to prescribe opioids associated with appointments that are behind schedule or later in the day compared with earlier or on-time appointments? Findings In this cross-sectional study, opioid prescribing for opioid-naive patients with pain diagnoses was significantly associated with increases as the workday progressed and with appointments that started late, although the effect size was modest. Nonopioid pain treatment order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 25 publications
0
47
1
Order By: Relevance
“…59 Comparable findings were observed for the prescription of opioids as well. 60 Similarly, one study found that clinicians' ordering of cancer screening tests decreased as the workday progressed. 61 Outside of healthcare, studies of how judges make decisions about parole, sentence lengths, and immigration have found that their decisions are sensitive to extraneous factors, including taking a food break, experiencing unexpected losses of football games, and an increase in outdoor temperature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…59 Comparable findings were observed for the prescription of opioids as well. 60 Similarly, one study found that clinicians' ordering of cancer screening tests decreased as the workday progressed. 61 Outside of healthcare, studies of how judges make decisions about parole, sentence lengths, and immigration have found that their decisions are sensitive to extraneous factors, including taking a food break, experiencing unexpected losses of football games, and an increase in outdoor temperature.…”
Section: Discussionmentioning
confidence: 98%
“…For example, one study found that clinicians are more likely to prescribe antibiotics to patients with upper respiratory tract infections as the workday progresses, probably because the cumulative cognitive demand of clinical decisions progressively impairs clinician’s ability to avoid clinically inappropriate decisions 59. Comparable findings were observed for the prescription of opioids as well 60. Similarly, one study found that clinicians’ ordering of cancer screening tests decreased as the workday progressed 61.…”
Section: Discussionmentioning
confidence: 99%
“…21 22 Patients in such circumstances could find themselves pressured into detrimental patterns of self-medication and delayed healthcare access. Consequently, 'quick fix' solutions such as self-medication or antibiotic purchase without prescriptions can be interpreted as default strategies to cope with adversity, [23][24][25] or perhaps even as 'performance enhancers'. 26 Precarity could therefore challenge the underlying assumptions and ultimately the effectiveness of public awareness campaigns that form the backbone of global AMR strategies ('Only take antibiotics prescribed to you').…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…Institutional constraints also play a role in doctors’ treatment decisions. Some evidence suggests that doctors are more likely to over-treat pain during periods of increased time-pressure, such as when it is late at night or when emergency departments are crowded [ 15 , 23 ]. Such time constraints may intensify doctors’ implicit biases by increasing their likelihood to rely on implicit assumptions about patient diagnostic categories to inform treatment [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%